2022
DOI: 10.21523/gcj3.2022060102
|View full text |Cite
|
Sign up to set email alerts
|

The Hydrogeological Behavior of Springs in Face of Rainfall Fluctuations in the Plain of Fez and its Middle Atlas Border, Morocco

Abstract: The scarcity of water resources presents the most threatening risk and its effects are beginning to affect several regions of the planet. It cannot be denied that Morocco, due to its location in the south of the Mediterranean, has been affected by these climatic trends of which the plateau de Sais offers a good example by its location in the center of the country and by its wealth of superficial and groundwater resources. In recent decades, this plateau has experienced water stress, particularly in its groundw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Taibi & Souag (2012) analysed more than 100 precipitation time series in northern Algeria and found a significant decrease in annual precipitation in north-western Algeria beginning in the 1970s. Qadem et al (2019) reported that mean annual precipitation was nearly 200 mm lower from 1980 to 2015 than that at the beginning of the 20th century in the Fes-Meknes region of Morocco. Several other studies in the Mediterranean region showed a negative trend in precipitation in Algeria (Meddi et al 2010), Spain (Herrera et al 2010;Sinoga et al 2011), Italy (Caloiero et al 2011) and Tunisia (Kingumbi et al 2005).…”
Section: Variability Changes and Breakpoints In Hydrology And Climate...mentioning
confidence: 99%
See 1 more Smart Citation
“…Taibi & Souag (2012) analysed more than 100 precipitation time series in northern Algeria and found a significant decrease in annual precipitation in north-western Algeria beginning in the 1970s. Qadem et al (2019) reported that mean annual precipitation was nearly 200 mm lower from 1980 to 2015 than that at the beginning of the 20th century in the Fes-Meknes region of Morocco. Several other studies in the Mediterranean region showed a negative trend in precipitation in Algeria (Meddi et al 2010), Spain (Herrera et al 2010;Sinoga et al 2011), Italy (Caloiero et al 2011) and Tunisia (Kingumbi et al 2005).…”
Section: Variability Changes and Breakpoints In Hydrology And Climate...mentioning
confidence: 99%
“…Ribes et al (2019) found that extreme precipitation events from 1961 to 2015 have significantly increased by a mean value of 22% in the Mediterranean region of France, while Tramblay et al (2012) reported no significant trends for the extreme precipitation over the same period in Morocco. Nevertheless, in Morocco, Amraoui et al (2011) reported a decrease in annual precipitation since the 1970s, and Singla et al (2010), Taibi & Souag (2012) and Qadem et al (2019) highlighted a significant breakpoint in mean annual precipitation. Then, while climate changes are effective at the scale of the Mediterranean region, due to the high heterogeneity of the climate, local trends in the precipitation amount or regime vary greatly.…”
Section: Introductionmentioning
confidence: 97%
“…Although these water reservoirs have proven crucial, they are not exempt from modern-day challenges. The karstic aquifers of the Middle Atlas, as described by Tennevin in his 1978 study, along with the Plio-Quaternary and Liassic aquifers in the Saïs region studied by Belhassan et al (2010) and Charroud et al (1978), are beginning to display increasing signs of vulnerability (Qadem et al, 2022). which derives from changes in climate as well as influences spurred by human activities.…”
Section: Study Areamentioning
confidence: 94%
“…The methodology is built upon the application of RS and GIS, targeting the evaluation of potential groundwater areas (GWP), rendering them indispensable in efforts to enhance water availability in the Saïs Plateau and the surrounding territories in the Middle Atlas -areas persistently grappling with water scarcity. This work focuses on the spatial visualization of water level fluctuations in aquifer storage areas, aiming to optimize groundwater resource management in these regions in Morocco, noted for their abundant groundwater reserves (Howell et al, 2019;Qadem et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation